2021
DOI: 10.3390/ijerph18052370
|View full text |Cite
|
Sign up to set email alerts
|

The Association of White Blood Cells and Air Pollutants—A Population-Based Study

Abstract: The links of air pollutants to health hazards have been revealed in literature and inflammation responses might play key roles in the processes of diseases. WBC count is one of the indexes of inflammation, however the literature reveals inconsistent opinions on the relationship between WBC counts and exposure to air pollutants. The goal of this population-based observational study was to examine the associations between multiple air pollutants and WBC counts. This study recruited community subjects from Kaohsi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 53 publications
(31 reference statements)
2
6
0
Order By: Relevance
“…Past studies showed that PM exposure was accompanied by elevated immune cell counts in bronchoalveolar lavage fluid, which implied an increased inflammatory burden in the lungs, but the evidence for the inflammatory response in the circulatory system was inconsistent. Two studies showed partly consistent results for PM 2.5 53 and NO 2, 54 the reduction of inflammation levels in these studies might be explained by the movement of immune cells from the bloodstream to stressed tissues such as the lungs.…”
Section: Discussionsupporting
confidence: 52%
“…Past studies showed that PM exposure was accompanied by elevated immune cell counts in bronchoalveolar lavage fluid, which implied an increased inflammatory burden in the lungs, but the evidence for the inflammatory response in the circulatory system was inconsistent. Two studies showed partly consistent results for PM 2.5 53 and NO 2, 54 the reduction of inflammation levels in these studies might be explained by the movement of immune cells from the bloodstream to stressed tissues such as the lungs.…”
Section: Discussionsupporting
confidence: 52%
“…Therefore, it was suggested that the increase in the number of these cells may be due to a rather non-specific response to physical stress / exercise rather than exposure to smoke (Swiston et al 2008 ). However, the relationship between air pollution and white blood cell counts, and hence its possible impact on the systemic inflammatory response, was also confirmed in a study examined of over 10,000 Taiwanese people (Hung et al 2021 ). On the other hand, an increase in the concentration of IL-6, IL-8, and the count of immature neutrophils was observed only after smoke exposure, suggesting the development of an exposure-induced systemic inflammation (Swiston et al 2008 ).…”
Section: Airway and Systemic Inflammation In Firefightersmentioning
confidence: 81%
“…An experimental study on rats exposed to fly ash from incinerators also showed a significant increase in monocyte counts in these rats [39]. In addition, a community-based study in China on outdoor air pollution and white blood cells revealed that the value of monocytes might be a function of the chemical nature of the particles [40]. According to this study, the number of monocytes in the exposed population could be increased under short-term (within one week) exposure of carbon monoxide (CO), but would be decreased when subjects are more exposed to sulfur dioxide (SO2).…”
Section: Discussionmentioning
confidence: 97%